BASIC LIVING AID TRAINING IMPROVES KNOWLEDGE AND READINESS TO HELP ONLINE OJEK DRIVERS IN COSTAL AREAS - Widyastuti, Merina; Maharani, Amalia; Priyantini, Dwi; Rustini, Sri Anik; Sari, Ninik Ambar (Community Service Journal of Indonesia, 2024)
Cardiac arrests have occurred very frequently in recent times, but not all members of the public can recognize the signs and symptoms and how to treat them. A heart attack is an emergency condition and requires quick and immediate action to prevent death. Proper education in early recognition of symptoms and how to treat them is very important because the time needed to take a patient to the hospital is often a problem. The aim of community service is to provide education and training to the online motorcycle taxi driver community in providing basic life support. This research design uses analytical observational with a cross sectional approach. The accidental sampling technique obtained 100 online motorcycle taxi drivers in the city of Surabaya. Evaluation measuring tool with questionnaires. Training is given for 2 days with blended learning. Data were analyzed using the Spearman Rho Test with significance (ρ ≤ 0.05). The components measured are knowledge and readiness to help From the results, it was found that 56% of online motorcycle taxi drivers had good knowledge, and 44% of drivers had sufficient knowledge. For readiness to help, it was found that 76% of drivers showed very good readiness to help, and 24% of drivers showed sufficient readiness. The results of the Spearman Rho statistical test show a p-value of 0.001 (ρ < 0.05), thus there is significance between the provision of training and the level of knowledge of basic life support and readiness to help among online motorcycle taxi drivers in costal areas of Surabaya. The community plays an important role in helping victims before they are treated by health workers. One part of society that often witnesses incidents on the road is online motorcycle taxi drivers. With good knowledge and readiness to help, it is hoped that community resilience will be formed that is responsive to everyday emergency conditions.